Strategy to improve economic condition of fishermen living in the coastal area in Kabupaten Pesisir Selatan - Firwan wan Tan; Lisa Nesti; Efa Yonnedi Yonnedi; Endrizal Ridwan Ridwan (Journal of Business and Socio-Economic Development, 2023)
Purpose – This research aims to study the economic conditions of fishermen living in the coastal area of Kabupaten Pesisir Selatan. Design/methodology/approach – The method used is a descriptive analysis method supported by a participatory planning method. The importance of primary data is to understand deeply the real problems of fishermen in the field, collected by using a survey method such as field observations, in-depth interviews by gathering fishermen and related stakeholders in the area, undertaking forum group discussion, workshop and seminar. Secondary data are necessary to support the primary data analysis. Findings – The results showed that there is an abundance of marine resources, but the economic condition of fishermen is far from expected. The income from fishing is not enough to feed their family's daily needs due to low catching productivity and raw fish selling price. The regency government and province do not have clear and concrete policies to resolve firmly and thoroughly the economic problems of fishermen living in the coastal areas. Research limitations/implications – This study succeeds in providing two breakthrough strategic policies to improve the economic conditions of fishermen, i.e. institutional and entrepreneurial innovations. Practical implications – Both strategic policies have a mutual relationship. Therefore, the implementations have to integrate with one another and be executed simultaneously in a single coastal area management system. Social implications – Bupati as a top policymaker in this region must take full responsibility for the successful implementation of these two strategic policies. Originality/value – Providing new ideas to solve the main problem of fishermen living in the coastal area in Indonesia.